Bulk and Surface Excitons in Alloyed and Phase-Separated ZnO-MgO Particulate Systems - Zhang, Huanjun; Gheisi, Amirreza; Sternig, Andreas; Mueller, Knut; Schowalter, Marco; Rosenauer, Andreas; Diwald, Oliver; Maedler, Lutz (ACS Applied Materials and Interfaces, 2012)
The rational design of composite nanoparticles with desired optical and electronic properties requires the detailed analysis of surface and bulk contributions to the respective overall function. We use flame spray pyrolysis (FSP) to generate nanoparticles of the ternary Zn–Mg–O system the compositions of which range from solid solutions of Zn2+ ions in periclase MgO to phase separated particle mixtures which consist of periclase (cubic) MgO and wurtzite (hexagonal) ZnO phases. The structure and composition of the composite ZnxMg1–xO (0 łeq x łeq 0.3) particles are investigated using X-ray diffraction and high-resolution transmission electron microscopy, whereas UV diffuse reflectance and photoluminescence (PL) spectroscopy are used for the investigation of their optical properties. Vacuum annealing has been carried out to track the effects of stepwise elimination of surface adsorbates on the photoexcitation and PL emission properties. We demonstrate that for Zn0.1Mg0.9O particles, the admixed ZnO suppresses the MgO specific surface excitons and produces a PL emission band at 470 nm. Although gaseous oxygen partially reduces the emission intensity of hydroxylated particles, it leads to entire quenching in completely dehydroxylated samples after vacuum annealing at 1173 K. Consequently, surface hydroxyls at the solid–gas interface play a significant role as protecting groups against the PL-quenching effects of O2. The obtained results are relevant for the characterization of ZnO-based devices as well as for other metal oxide materials where the impact of the surface composition on the photoelectronic properties is usually neglected.
EAM Import::2019-03-13

Cubes to Cubes: Organization of MgO Particles into One-Dimensional and Two-Dimensional Nanostructures - Thomele, Daniel; Baumann, Stefan O.; Schneider, Johannes; Sternig, Andreas; Shulda, Sarah; Richards, Ryan M.; Schwab, Thomas; Zickler, Gregor A.; Bourret, Gilles R.; Diwald, Oliver (Crystal Growth and Design, 2021)
Developing simple, inexpensive, and environmentally benign approaches to integrate morphologically well-defined nanoscale building blocks into larger high surface area materials is a key challenge in materials design and processing. In this work, we investigate the fundamental surface phenomena between MgO and water (both adsorption and desorption) with particles prepared via a vapor-phase process (MgO nanocubes) and a modified aerogel process (MgO(111) nanosheets). Through these studies, we unravel a strategy to assemble individual MgO nanoparticles into extended faceted single-crystalline MgO nanosheets and nanorods with well-defined exposed surfaces and edges. This reorganization can be triggered by the presence of H2O vapor or bulk liquid water. Water adsorption and the progressive conversion of vapor-phase grown oxide particles into hydroxides give rise to either one-dimensional or two-dimensional (1D or 2D) structures of high dispersion and surface area. The resulting Mg(OH)2 lamella with a predominant (001) surface termination are well-suited precursor structures for their topotactic conversion into laterally extended and uniform MgO(111) grain surface configurations. To understand the potential of polar (111) surfaces for faceting and surface reconstruction effects associated with water desorption, we investigated the stability of MgO(111) nanosheets during vacuum annealing and electron beam exposure. The significant surface reconstruction of the MgO(111) surfaces observed shows that adsorbate-free (111)-terminated surfaces of unsupported MgO nanostructures reconstruct rather than remain as charged planes of either three-fold coordinated O2- ion or Mg2+ ions. Thus, here we demonstrate the role water can play in surface formation and reconstruction by bridging wet chemical and surface science inspired approaches.
CRIS-Team Scopus Importer:2021-08-06

Delamination and Dissolution of Titanate Nanowires: A Combined Structure and in Situ Second Harmonic Generation Study - Schürer, Benedikt; Elser, Michael J.; Sternig, Andreas; Peukert, Wolfgang; Diwald, Oliver (Journal of Physical Chemistry C, 2011)
Mechanistic insights into shape and structure transformation of metal oxide nanostructures are critical to our understanding of how synthesis parameters and chemical environment affect their properties. Na2Ti3O7 nanowires, which are composed of titanate nanosheets and which contain sodium ions in the interlayer region, are thermodynamically unstable in acid solutions. At room temperature nanosheet delamination along the nanowire length axis leads to coiled-up nanoscrolls. At 373 K, a dissolution and TiO2 recrystallization process gives rise to colloidal anatase nanoparticles. The impact of temperature on different reaction pathways is attributed to differences in the energy barriers associated with the two transformation channels. We comprehensively investigated these reactions with X-ray diffraction and electron microscopy and for the first time tracked processes at the solid–liquid interface such as nanosheet delamination by time-resolved second harmonic generation (SHG) measurements. The applicability of the SHG method for in situ studies which address the transformation of layered nanostructures in aqueous solution even at high electrolyte concentrations is demonstrated.

Exciton Formation at Solid-Solid Interfaces: a systematic experimental and ab initio Study on compressed MgO Nanopowders - Sternig, Andreas; Koller, David; Siedl, Nicolas; Diwald, Oliver; Mckenna, Keith (Journal of Physical Chemistry C, 2012)
An important and so far neglected class of structural elements affecting the overall properties of metal oxide nanopowders are interfaces between individual nanocrystals. In this work we show experimentally that these defects inside a powder of compressed MgO nanocubes are subject to photoexcitation in the UV light range. In particular, we identify a so far unobserved photoluminescence emission process at 2.5 eV. First principles calculations of the optical properties of nanocrystal interfaces provide plausible candidates for both light absorbing and emitting sites which involve different types of interface features. It was found that edge dislocations that arise from interfaces between nanocube edges and terraces induce a significant electrostatic perturbation of the interfacial electronic states. This leads to exciton generation and luminescence at even lower energies than those related to corners and edges of MgO nanocubes
EAM Import::2019-03-14

O2 adsorption dependent photoluminescence emission from metal oxide nanoparticles - Gheisi, Amirreza; Neygandhi, Chris; Sternig, Andreas; Carrasco, Esther; Marbach, Hubertus; Thomele, Daniel; Diwald, Oliver (Physical Chemistry Chemical Physics, 2014)
Optical properties of metal oxide nanoparticles are subject to synthesis related defects and impurities. Using photoluminescence spectroscopy and UV diffuse reflectance in conjunction with Auger electron spectroscopic surface analysis we investigated the effect of surface composition and oxygen adsorption on the photoluminescence properties of vapor phase grown ZnO and MgO nanoparticles. On hydroxylated MgO nanoparticles as a reference system, intense photoluminescence features exclusively originate from surface excitons, the radiative deactivation of which results in collisional quenching in an O2 atmosphere. Conversely, on as-prepared ZnO nanoparticles a broad yellow emission feature centered at h extgreeknEm = 2.1 eV exhibits an O2 induced intensity increase. Attributed to oxygen interstitials as recombination centers this enhancement effect originates from adsorbate-induced band bending, which is pertinent to the photoluminescence active region of the nanoparticles. Annealing induced trends in the optical properties of the two prototypical metal oxide nanoparticle systems, ZnO and MgO, are explained by changes in the surface composition and underline that particle surface and interface changes that result from handling and processing of nanoparticles critically affect luminescence.
EAM Import::2019-03-08

On the entangled growth of NaTaO3 cubes and Na2Ti3O7 wires in sodium hydroxide solution - Baumann, Stefan O.; Liu, Chang; Elser, Michael J.; Sternig, Andreas; Siedl, Nicolas; Berger, Thomas; Diwald, Oliver (Chemistry - A European Journal, 2013)
The entangled growth of sodium titanate Na2Ti3O7 nanowires and sodium tantalate NaTaO3 cubes was investigated with electron microscopy, X‐ray diffraction, and UV diffuse reflectance spectroscopy. Depending on the composition of the Ta2O5‐ and TiO2‐particle‐based powder mixtures, which served as educts, we observed different types of hybridization effects. These include the titanium‐induced contraction of the NaTaO3 perovskite‐type unit cell and the generation of electronic defect states in NaTaO3 that give rise to optical subbandgap transitions and tantalum‐induced limitations of the Na2Ti3O7 nanowire growth. The transformation from Ta2O5 to NaTaO3 occurs through a dissolution–recrystallization process. A systematic analysis of the impact of different titanium sources on NaTaO3 dispersion and, thus, on the properties of the entangled nanostructures revealed that a perfect intermixture of cubes and nanowires can only be achieved when titanate nanosheets emerge during transformation as reaction intermediates and shield nucleation and growth of isolated NaTaO3 cubes. The here demonstrated approach can be highly instrumental for understanding the nucleation and growth of composite and entangled nanostructures in solution and—at the same time—provides an interesting new class of photoactive composite material
Keywords: nanostructures; optical properties; crystal growth; doping; tantalum

Optical Properties of Nanocrystal Interfaces in Compressed MgO Nanopowders - Mckenna, Keith P.; Koller, David; Sternig, Andreas; Siedl, Nicolas; Govind, Niranjan; Sushko, Peter V.; Diwald, Oliver (ACS nano, 2011)
The optical properties and charge trapping phenomena observed on oxide nanocrystal ensembles can be strongly influenced by the presence of nanocrystal interfaces. MgO powders represent a convenient system to study these effects due to the well-defined shape and controllable size distributions of MgO nanocrystals. The spectroscopic properties of nanocrystal interfaces are investigated by monitoring the dependence of absorption characteristics on the concentration of the interfaces in the nanopowders. The presence of interfaces is found to affect the absorption spectra of nanopowders more significantly than changing the size of the constituent nanocrystals and, thus, leading to the variation of the relative abundance of light-absorbing surface structures. We find a strong absorption band in the 4.0-5.5 eV energy range, which was previously attributed to surface features of individual nanocrystals, such as corners and edges. These findings are supported by complementary first-principles calculations. The possibility to directly address such interfaces by tuning the energy of excitation may provide new means for functionalization and chemical activation of nanostructures and can help improve performance and reliability for many nanopowder applications.
EAM Import::2019-03-08

Phase separation at the nanoscale: Structural properties of BaO segregates on MgO-based nanoparticles - Sternig, Andreas; Klacar, Simon; Bernardi, Johannes; Stoeger-Pollach, Michael; Gronbeck, Henrik; Diwald, Oliver (Journal of Physical Chemistry C, 2011)

Photoluminescence quenching in compressed MgO nanoparticle systems - Siedl, Nicolas; Koller, David; Sternig, Andreas; Thomele, Daniel; Diwald, Oliver (Physical Chemistry Chemical Physics, 2014)

Size effects in MgO cube dissolution - Baumann, Stefan O.; Schneider, Johannes; Sternig, Andreas; Thomele, Daniel; Stankic, Slavica; Berger, Thomas; Gronbeck, Henrik; Diwald, Oliver (Langmuir, 2015)
Stability parameters and dissolution behavior of engineered nanomaterials in aqueous systems are critical to assess their functionality and fate under environmental conditions. Using scanning electron microscopy, transmission electron microscopy, and X-ray diffraction, we investigated the stability of cubic MgO particles in water. MgO dissolution proceeding via water dissociation at the oxide surface, disintegration of Mg2+–O2– surface elements, and their subsequent solvation ultimately leads to precipitation of Mg(OH)2 nanosheets. At a pH ≥ 10, MgO nanocubes with a size distribution below 10 nm quantitatively dissolve within few minutes and convert into Mg(OH)2 nanosheets. This effect is different from MgO cubes originating from magnesium combustion in air. With a size distribution in the range 10 nm ≤ d ≤ 1000 nm they dissolve with a significantly smaller dissolution rate in water. On these particles water induced etching generates (110) faces which, above a certain face area, dissolve at a rate equal to that of (100) planes.1 The delayed solubility of microcrystalline MgO is attributed to surface hydroxide induced self-inhibition effects occurring at the (100) and (110) microplanes. The present work underlines the importance of morphology evolution and surface faceting of engineered nanomaterials particles during their dissolutio

Solar Light and Dopant-Induced Recombination Effects: Photoactive Nitrogen in TiO2 as a Case Study - D'Arienzo, Massimiliano; Siedl, Nicolas; Sternig, Andreas; Scotti, Roberto; Morazzoni, Franca; Bernardi, Johannes; Diwald, Oliver (Journal of Physical Chemistry C, 2010)
The spectral response of newly synthesized and doped TiO_2 nanostructures, which are designed for the operation under solar light, is key to their potential performance as photocatalyst materials. In the case of nitrogen-doped TiO_2 particles, the presence of the photoactive defect can be verified via characteristic spectroscopic fingerprints, such as (1) an optical absorption band above extgreekl > 400 nm, (2) paramagnetic defect states related to substitutional and interstitial nitrogen atoms, and (3) a photoluminescence emission feature that can be induced by band gap excitation. We report these spectroscopic fingerprints for hydrothermally derived and N-doped TiO_2 powder samples. On the basis of defined annealing procedures, we also found a way to eliminate the photoactive nitrogen defects and performed light-induced charge separation experiments on samples before and after dopant elimination in O_2 atmosphere. The concentrations of adsorbed O_2 - ions, which stand for scavenged photogenerated electrons, were determined by electron paramagnetic resonance (EPR) spectroscopy. On the basis of these data, we calculated the number of photons, which (a) were additionally utilized because of the beneficial effect of photoactive nitrogen and (b) were lost because of the dopant-induced recombination of UV light generated charge carriers. As a major result, we found for the doped materials that both effects actually compensate each other. With regard to the synthesis and characterization of doped TiO_2 systems, these findings underline the importance to include dopant-induced charge-carrier recombination effects in the evaluation of the photocatalyst's spectral response in order to reach a fair evaluation of its properties.
EAM Import::2019-03-13

Spontaneous Growth of Magnesium Hydroxide Fibers at Ambient Conditions - Gheisi, Amirreza; Sternig, Andreas; Rangus, Mojca; Redhammer, Günther; Hartmann, Martin; Diwald, Oliver (Crystal Growth & Design, 2014)
Spontaneous transformation paths of nanomaterials point to guiding, principles for synthesis. We describe the room temperature transformation of MgO nanocubes into Mg-3(OH)(5)Cl center dot 4H(2)O nanofibers in air and investigated the underlying formation mechanism using electron microscopy, X-ray diffraction, and solid-state NMR spectroscopy. Upon contact with water vapor, the magnesium hydroxide needles were found to grow out of agglomerates of highly dispersed MgO nanocubes with preadsorbed SiCl4. Corresponding one-dimensional nanostructures do not form on low surface area materials. The presented growth approach is potentially extendable to other hydrolyzable metal oxides at ultrafine dispersion.

Surface decoration of MgO nanocubes with sulfur oxides: Experiment and theory - Sternig, Andreas; Diwald, Oliver; Gross, Silvia; Sushko, Peter V. (Journal of Physical Chemistry C, 2013)

Surface exciton separation in photoexcited MgO nanocube powders - Sternig, Andreas; Stankic, Slavica; Mueller, Markus; Siedl, Nicolas; Diwald, Oliver (Nanoscale, 2012)
In MgO nanocube powders surface excitons can separate and the resulting charge carriers provide reactive adsorption sites at well-defined surface elements. We employed photoluminescence (PL) emission bands originating from the photoexcitation of nanocube corners and edges as quantitative probes to explore their chemical reactivity towards molecular hydrogen. Surface excitons which form at corners and edges exhibit similar cross-sections for separation in vacuum. The separation of edge excitons, however, is significantly enhanced in hydrogen atmosphere when hydrogen adsorption occurs as a simultaneous surface process. The electronic structure of MgO nanocube edges which split hydrogen heterolytically upon generation of surface hydroxyls and hydrides is unaffected by the photoexcitation of corners. Respective edges, however, are efficient absorption sites for UV photons. Transfer of exciton energy to oxygen ions in corners is followed by exciton separation which transforms corner ions into surface radicals leading to a well-defined starting point for the site selective functionalization of metal oxide nanostructures.
Keywords: nanoparticle

Surface-specific visible light luminescence from composite metal oxide nanocrystals - Sternig, Andreas; Bernardi, Johannes; Mckenna, Keith; Diwald, Oliver (Journal of Materials Science, 2015)
Low-coordinated surface elements on metal oxide nanoparticles represent the basis for a new concept of luminescent nanoparticles made of abundant, non-toxic, and thermally stable materials. This combined experimental and theoretical study describes the generation and stability of Ba-doped MgO nanoparticle surfaces and their optical absorption and luminescence dependence on Ba loading. It is demonstrated that the vapor phase growth process employed here represents a particularly robust synthesis approach for particle powders with reproducibly adjustable photoluminescence emission properties in the range between blue and yellow light. Moreover, this in-depth characterization also provides an understanding of the electronic and optical characteristics of this nanoparticulate material with a so far unnoticed potential for solid-state light applications that are based on down conversion of UV ligh

Thin water films and magnesium hydroxide fiber growth - Gheisi, Amirreza; Sternig, Andreas; Redhammer, Guenther J.; Diwald, Oliver (RSC Advances, 2015)
Thin films of water covering highly dispersed metal oxides can give rise to the spontaneous and spatially controllable growth of hydroxide fibers in ambient air. Knowledge about the underlying formation mechanisms is key to the rational development of metal oxide nanomaterials and associated microstructures. We used SiCl4 as a water free chlorine ion source for the surface functionalization of MgO nanocubes and explored their subsequent transformation into magnesium oxychloride Mg3(OH)5Cl·4H2O fibers upon contact with water vapor. Specifically we show how the temperature of the functionalization process and material dispersion control the reaction pathway that can lead to very different products like Mg(OH)2, MgCl2·6H2O, or Mg3(OH)5Cl·4H2O and delineate a reaction mechanism. Lessons to be learned from this unique route to form hydroxide fibers under ambient conditions can be applied to a variety of microstructural evolution processes that involve metastable solids and superficial water acting both as a reactant and as a reaction medium for the hydration of metal oxide particle

Zinc oxide scaffolds on MgO nanocubes - Stankic, Slavica; Sternig, Andreas; Finocchi, Fabio; Bernardi, Johannes; Diwald, Oliver (Nanotechnology, 2010)
Powders of isolated and well-dispersed oxide nanocubes are promising components for photoelectronic applications that benefit from tunable optical properties, surface reactivity and the ease of realization of their controlled assembly. Here, we demonstrate that combustion of zinc and magnesium metal vapors at reduced pressures followed by subsequent vacuum annealing of the resulting nanoparticle powders yields single-crystalline ZnxMg1 - xO nanocubes of exceptional regular cubic shape and edge lengths below 25 nm. In line with ab initio calculations, which predict preferential Zn2 + segregation into low coordinated surface elements of the MgO nanocubes, we track the occupation of edge sites by chains of Zn2 + –O2 - units through their spectroscopic signatures. As a method to generate composite nanostructures with controlled spatial distribution of the chemical components, the annealing induced ion segregation can be extended to other well-dispersed metastable nanoparticles. We expect that the energy of segregation mainly depends on the site coordination number, which can promote controlled demixing within the nanoparticles
EAM Import::2019-03-12